Global DNA hypermethylation pattern and unique gene expression signature in liver cancer from patients with Indigenous American ancestry - Cerapio, Juan Pablo (2021)
This work was supported by the Alliance pour les Sciences de la Vie et de la Santé (AVIESAN), ITMO Cancer ENV201408 (to S.B.) and the Ligue Contre le Cancer (to P.P.). J.P.C. was a recipient of a doctoral scholarship from the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FONDECYT) 212-2015-FONDECYT and was supported by a fellowship from Campus France 941211E; L.C. was supported by a doctoral fellowship from IRD ARTS-2016-878573B; I.L. was supported by a postdoctoral fellowship from the Fondation ARC pour la Recherche sur le Cancer PDF20170505624; J.J.F. has received funding from the Agence Nationale de la Recherche (ANR) under the Investments for the Future program 11-LABX-0068; S.C.Z. and E.R. have received funding from the World Bank Group and FONDECYT-CONCYTEC under the Research Infrastructure Improvement program 016-2018-FONDECYT/BM; and S.B. has received funding from the European Union’s Horizon 2020 Framework program under the Marie Skłodowska-Curie Actions 823935.